Efficient treatment of lead-containing wastewater by hydroxyapatite/chitosan nanostructures - Ahmad M. Mohammad (Arabian Journal of Chemistry, 2017)
The development of hydroxyapatite nanorods (nHAp) and hydroxyapatite/chitosan nanocomposite (nHApCs) was sought as potential sorbents for the removal of lead ions from aqueous lead-containing solutions in a batch adsorption experiment. The high resolution transmission electron microscopy, energy dispersive X-ray analysis, X-ray diffraction, Fourier transform infrared spectrophotometry and Zeta potential measurements were all combined to reveal the morphology, composition, crystal structure, functionality and stability of the prepared sorbents. The equilibrium concentration of Pb2+ ions was identified by the atomic absorption spectrophotometry. The kinetics of the sorption process was investigated together with the influence of initial lead ions concentration, sorbent dosage and solution pH on the sorption capacity. The sorption process followed pseudo-second-order kinetics, where 20 min was quite enough to attain equilibrium. Two models of adsorption isotherms (Freundlich and Langmuir) were employed to correlate the data in order to understand the adsorption mechanism. Interestingly, in one of the experiments, for a 200 mL solution (pH = 5.6) containing 100 ppm lead ions, a sorbent dosage of 0.4 g nHAp could achieve a complete removal for lead ions. However, typically, the sorption capacities of nHAp and nHApCs to lead ions were 180 and 190 mg/g respectively, which appear excellent for lead removal.